Fatigue life prediction on critical component for structure life extension of X - aircraft - Kamarulazizi, Sulaiman; Venugopal, Arvinthan; Harmin, Mohammad Yazdi; Abdullah Sani, Mohd Norhasani; Ali, Alizarin (The Aeronautical and Astronautical Society of the Republic of China, 2024)
Critical aircraft components, such as load-bearing structures, are integral to an aircraft's overall integrity. Factors like fatigue loading, operational conditions, and environmental wear necessitate continuous structural assessment for airworthiness. The Royal Malaysian Air Force (RMAF) employs the Aircraft Structure Integrity Program (ASIP) in tandem with the Safe Life fatigue design concept for ongoing structural integrity monitoring. RMAF's Efforts encompass engineering analyses and task cards, focusing on critical aircraft components. Various Computer-Aided Engineering (CAE) techniques, including fatigue analysis and Low Cycle Fatigue characterization, are applied. Numerical simulations with NX Nastran are used to predict fatigue behavior and failure points, with specific emphasis on the wing root's susceptibility to fatigue failure among six critical areas. Results indicate the wing root's remarkable structural resilience, even with up to a 30 thickness reduction in aluminum components, potentially extending the structural lifespan up to 100 years. This research endeavors to enhance the aircraft's wing structure's operational longevity, underscoring its robust design and commitment to aviation safety through thickness reduction fatigue analysis on the aluminum part of the wing root structure. These findings highlight meticulous engineering analysis and computational methodologies that elevate aircraft safety and compliance with stringent airworthiness standards.